PENGARUH MOTIVASI DAN PENGETAHUAN TERHADAP MINAT INVESTASI DI PASAR MODAL PADA MAHASISWA - Richo Elfrizal Ar Rahman; Waspodo Tjipto Subroto (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2022)
Managing personal finances is not an easy thing for students due to the growing phenomenon of consumptive behavior. Even though they have been equipped with knowledge through courses on financial institutions and capital markets, students seem desperate to invest in the capital market due to several factors. This study aims to explain the effect of motivation and knowledge on interest in investing in the capital market in Students of the Economics Education Study Program, State University of Surabaya. This research uses quantitative methods. Determining the research population used a purposive sampling technique, namely students of the 2018 economics study program, a total of 62 students. Collecting data using a questionnaire. The analytical method uses multiple linear regression analysis with the help of the SPSS 24 for windows program. The results of this study indicate that there is a positive effect of motivation on investment interest in the capital market, there is a positive effect of knowledge on investment interest in the capital market and simultaneously motivation and knowledge have a positive effect on investment interest in the capital market in Unesa Economics Education Study Program students.Mengelola keuangan pribadi bukanlah hal yang mudah bagi mahasiswa dikarenakan fenomena perilaku konsumtif yang berkembang. Walaupun sudah dibekali pengetahuan melalui mata kuliah lembaga keuangan dan pasar modal, mahasiswa terkesan putus asa untuk berinvestasi di pasar modal karena beberapa faktor. Penelitian ini bertujuan untuk menjelaskan pengaruh motivasi dan pengetahuan terhadap minat investasi di pasar modal pada mahasiswa Prodi Pendidikan Ekonomi Universitas Negeri Surabaya. Penelitian ini menggunakan metode kuantitatif. Penentuan populasi penelitian menggunakan teknik purposive sampling yaitu mahasiswa prodi pendidikan ekonomi angkatan 2018 yang berjumlah 62 mahasiswa. Pengumpulan data menggunakan kuesioner. Metode analisis menggunakan analisis regresi linier berganda dengan bantuan program SPSS 24 for windows. Hasil penelitian ini menunjukan terdapat pengaruh positif motivasi terhadap minat investasi di pasar Modal, terdapat Pengaruh positif pengetahuan terhadap minat investasi di pasar modal dan secara simultan Motivasi dan pengetahuan berpengaruh positif terhadap Minat Investasi di Pasar Modal pada mahasiswa Prodi Pendidikan Ekonomi Unesa.